THE BACKGROUND OF MARKET IDEOLOGY IN THE DEVELOPMENT OF BELADIRI AIKIDO IN BALI - Nurita, Wayan; Suarka, I Nyoman; Wirawan, AA Bagus; Dhana, I Nyoman (E-Journal of Cultural Studies; Volume 10, Number 2, May 2017DO - 10.24843/cs.2017.v10.i02.p03, 2017)
Quite a lot of Balinese people nowadays are pursuing different martial arts coming from other nations, among others is Aikido . Aikido as one of the martial arts of Japan can be accepted and is growing well in Bali which has the background of market ideology as one of the impacts of globalization. The development process of Aikido in Bali both in addition to the number of training venues ( Dojo ) and improving the quality of the participants’ techniques ( Aikidoka ) under the supervisionof Bali Aikido Master Organization ( Bari Aikikai ) which has been established since 1997. By questioning what kind of ideology is working in the development of Aikido Martial Arts in Bali, this research is a qualitative research which applies the Hypereality theory of Jean Baudrillard. Result of the research shows that the development of aikido martial arts in Bali both in the development of the dojo and the aikidoka are in the process to reach certain levels. In order to reach both, the allocation of time and funds are required. Bari aikikai is a Japan subordinate of aikido martial arts organization (Nihon Aikikai). Everything related to the development of aikido martial art in Bali is done through Bari Aikikai.  The Japanese as the cultural owner and discourse producer play an important role in relation to the market ideology in it. This condition and realitycan be seen in the development process of aikido martial art in Bali. Both the dojo and aikidoka managers spend a lot of money in terms of training in the form of compulsory dues and other dues payment. This research also found a new paradigm that behind the acceptance and development of aikido martial artsas the globalization of culture, there is market ideology behind the discourse.